Promoting and Avoiding Recombination: Contrasting Activities of the Escherichia coli RuvABC Holliday Junction Resolvase and RecG DNA Translocase - Zhang, Jing (Genetics Society of America, 2010)
RuvABC and RecG are thought to provide alternative pathways for the late stages of recombination in Escherichia coli. Inactivation of both blocks the recovery of recombinants in genetic crosses. RuvABC resolves Holliday junctions, with RuvAB driving branch migration and RuvC catalyzing junction cleavage. RecG also drives branch migration, but no nuclease has been identified that might act with RecG to cleave junctions, apart from RusA, which is not normally expressed. We searched for an alternative nuclease using a synthetic lethality assay to screen for mutations causing inviability in the absence of RuvC, on the premise that a strain without any ability to cut junctions might be inviable. All the mutations identified mapped to polA, dam, or uvrD. None of these genes encodes a nuclease that cleaves Holliday junctions. Probing the reason for the inviability using the RusA Holliday junction resolvase provided strong evidence in each case that the RecG pathway is very ineffective at removing junctions and indicated that a nuclease component most probably does not exist. It also revealed new suppressors of recG, which were located to the ssb gene. Taken together with the results from the synthetic lethality assays, the properties of the mutant SSB proteins provide evidence that, rather than promoting recombination, a major function of RecG is to curb potentially pathological replication initiated via PriA protein at sites remote from oriC.